Effectiveness of cognitive behavioral conjoint therapy for posttraumatic stress disorder (PTSD) in a U.S. Veterans Affairs PTSD clinic. Issue 2 (23rd December 2021) - Pukay‐Martin, Nicole D.; Fredman, Steffany J.; Martin, Colleen E.; Le, Yunying; Haney, Alison; Sullivan, Connor; Monson, Candice M.; Chard, Kathleen M.
Abstract: Cognitive behavioral conjoint therapy (CBCT) for posttraumatic stress disorder (PTSD) is a 15‐session conjoint treatment for PTSD designed to improve PTSD symptoms and enhance intimate relationship functioning. Numerous studies of CBCT for PTSD document improvements in patient PTSD and comorbid symptoms, partner mental health, and relationship adjustment. However, little is known about its effectiveness in real‐world clinical settings. Using an intention‐to‐treat sample of couples who participated in CBCT for PTSD in an outpatient U.S. Veterans Affairs (VA) PTSD clinic ( N = 113), trajectories of session‐by‐session reports of veterans' PTSD symptoms and both partners' relationship happiness were examined. Across sessions, there were significant reductions in veteran‐rated PTSD symptoms, d = −0.69, and significant increases in veteran‐ and partner‐rated relationship happiness, d s = 0.36 and 0.35, respectively. Partner ratings of veterans' PTSD symptoms increased before significantly decreasing, d = −0.24. Secondary outcomes of veteran and partner relationship satisfaction, d s = 0.30 and 0.42, respectively; veteran and partner depressive symptoms, d s = −0.75 and −0.29, respectively; and partner accommodation of PTSD symptoms, d = −0.44, also significantly improved from pre‐ to posttreatment. The findings suggest that CBCT for PTSD was effective for decreasing PTSD and comorbid symptoms in veterans, as well as for improving relationship functioning and partners' mental health, among a sample of real‐world couples seeking treatment in a VA PTSD specialty clinic.